The perspective effect of awe in VR environments: a comparison of first-person and third-person perspectives - Otsubo, Hiromu; Lehnort, Marvin; Steininger, Melissa; Marquardt, Alexander; Dollack, Felix; Hirao, Yutaro; Perusquía-Hernández, Monica; Uchiyama, Hideaki; Kruijff, Ernst; Riecke, Bernhard; Kiyokawa, Kiyoshi (2023)
Nature scenes like landscapes have been used in several studies to evoke awe. Landscapes evoke awe due to their vastness and beauty, and they are an example of an awe-eliciting situation mentioned by many participants in several studies (Bai et al., 2017; Joye & Bolderdijk, 2015; Smalley & White, 2023). In Virtual Reality (VR) environments, the difference between first-person and third-person perspectives has been studied in dynamic tasks such as game tasks (Gorisse et al., 2017; Hoppe et al., 2022; Iriye & St. Jacques, 2021). However, little attention has been paid to the difference between static tasks, such as viewing landscapes, and interactive environments where the user has the freedom to move around. Also, the effect of perspective on complex emotions such as awe has not been empirically verified. Therefore, the purpose of this study is to measure the degree of awe felt when viewing different perspectives of static landscapes in VR environments, and to clarify the impact of perspective on awe.